Organometallic Osmium Arene Complexes with Potent Cancer Cell Cytotoxicity - Fu, Ying; Habtemariam, Abraha; Pizarro, Ana M; van Rijt, Sabine H; Healey, David J; Cooper, Patricia A; Shnyder, Steven D; Clarkson, Guy J; Sadler, Peter J (Journal of medicinal chemistry, 2010)
Iodido osmium(II) complexes [Os(η6-arene)(XY)I]+ (XY = p-hydroxy or p-dimethylaminophenylazopyridine, arene = p-cymene or biphenyl) are potently cytotoxic at nanomolar concentrations toward a panel of human cancer cell lines; e.g., IC50 = 140 nM for [Os(η6-bip)(azpy-NMe2)I]+ toward A2780 ovarian cancer cells. They exhibit low toxicity and negligible deleterious effects in a colon cancer xenograft model, giving rise to the possibility of a broad therapeutic window. The most active complexes are stable and inert toward aquation. Their cytotoxic activity appears to involve redox mechanisms.